Apprendre à philosopher au café : bilans et perspectives - Romain Jalabert (Nantes Université, 2012)
With the strength of about twenty years of existence and an extremely vast and diversified geographical presence, the phenomenon said of the"café philosophiques (coffees of philosophy) " has proved to be capable of denying the suspicions about "the effect of fashion" and of " Parisian snobbery " which were brought against it for a long time. Beyond the criticisms which do not die and the doubts as to its philosophic validity, the movement goes on living, evolves, without ever going away too much from the famous wish of Diderot: " let us hurry to make philosophy popular! ". The "café philosophique" is the unexpected leader of a variety of new practices (philosophy with movies, hikes of philosophy, banquets of philosophy, workshop of philosophy, within different settings as the Popular Universities, etc). Without any doubt, the "café philosophique" remains the most popular and the most well known of the " New Philosophic Practices ". But probably also the most attacked... We are studying how the "café philosophique" begun and the evolution of this movement in the city, and we are trying to conceive some perspectives for this practice, the most ancient among the New Philosophical Practices. This research is made with the consultation of works, articles of magazines, official reports and radio archives covering the period from 1992 to 2010. It is also based on a survey made on the basis of an electronic questionnaire, during the months of May and June 2010.